The American political party system : continuity and change over ten presidential elections - Jackson, John S., 1940- (Brookings Institution Press, 2014)
From party polarization, elections, and internal party politics, to the evolution of the U.S. presidency, John S. Jackson''s new book has something for everyone interested in American politics. Beginning with a discussion of the creation of the U.S. government to the formation of today''s political powerhouses, Jackson provides a narrative sweep of American party history like none other. Unique to this book is a detailed breakdown of the evolution of political parties from 1832 to the current era. Jackson explains how the reform era came to be, as well as how it produced the polarized party er.